Osnove verzologije - Bjelčevič, Aleksander (Jezik in slovstvo, 2016)
We describe and define two concepts: irregular accentual-syllabic (syllabotonic) verse and caesura. Irregular accentual-syllabic verse is a type of poetic composition in which lines of the same rhythm (e.g., iambic) but very different lengths (e.g., 4, 5, 7, 8, 11, 14 syllables) follow each other in an unpredictable order and have stanzas of variable lengths. This is not yet free verse, as it preserves iambic, trochaic or amphibrachic, etc. rhythm. In accentual-syllabic and syllabic versification, caesura is an obligatory word boundary at a fixed place in every line of a poem (in Serbo-Croatian deseterac and its trochaic imitations, it is after the 4th syllable). Therefore, caesura is not a pause. Slovenian metres with caesura are: trochaic 8-, 10-, 12-, 14-, 15-, 16-syllable lines with caesuras after the 8-th syllable; Nibelungen verse has a caesura after the 7th syllable, iambic 12-syllable alexandrine after the 6th syllable, amphibrachic 11- and 12-syllable lines after the 6th syllable, etc., whereas iambic pentameter has no caesura.
Keywords: Lithuanian Metrica; metrika; verz; iregularni verz; svobodni verz; jambski enajsterec; epski deseterec; cezura; slovenska poezija; Slovene literature; slovenska književnost